Prospective cohort study of surgical trainee experience of access to gastrointestinal endoscopy training in the UK and Ireland. (July 2019) - Patel, K.; Ward, S.; Gash, K.; Ferguson, H.; Mason, M.; McKay, S.C.; Kumar, B.; Sudlow, A.; Sutton, P.A.; Humm, G.; Mohan, H.M.
Abstract: Introduction: Surgical trainees are reporting barriers to training in gastrointestinal (GI) endoscopy. This snapshot survey aimed to gather data on variation in access to quality GI endoscopy training for Colorectal and Upper Gastrointestinal (GI) surgical trainees across the UK and Ireland. Materials and methods: An online 20-point survey was designed and distributed nationally to surgical trainee members of the Association of Surgeons in Training (ASiT), Dukes and The Roux Group (formerly Association of Upper Gastrointestinal Surgeons of Great Britain and Ireland Trainees). The survey was designed in collaboration with The Roux Group for Upper GI trainees and the Dukes' Club for Colorectal trainees. Results: 218 responses were received, most with a Colorectal or Upper GI sub-specialty interest (colorectal 56.0%; upper GI surgery 25.7%). Only 28.6% of trainees attended a dedicated training endoscopy list at least once a week with 28.1% not attending any at all. Less than half of trainees reported having endoscopy formally timetabled on rotas (36.9%). Most trainees (88.0%) encountered difficulties in gaining endoscopy training including lack of available lists (77.2%), conflicting operative commitments (59.4%), preferential allocation of lists to gastroenterology trainees (57.9%) and resistance from endoscopy departmental leads (38.6%). Regarding JAG accreditation, 77.1% respondents felt it should be mandatory prior to CCT with 80.3% believing this would lead to better access to dedicated endoscopy training equivalent to gastroenterology trainees. 93.1% trainees felt that attaining JAG accreditation by surgical trainees was important to patient care. Discussion: This study demonstrates significant barriers in accessing GI endoscopy training for general surgical trainees which urgently needs to be improved. In order to meet JAG training requirements for surgical trainees, a multifaceted collaborative approach from surgical and gastroenterology training bodies, local JAG trainers and the General Surgery SAC and JCST is required. This is to ensure that endoscopy is promoted and a robust model of training is successfully designed and delivered to general surgery trainees. Highlights: Endoscopy training opportunities are currently insufficient for trainees. Currently less than one-quarter of senior trainees are JAG accredited in the relevant endoscopy for their subspecialty by the time they complete their training. More focused delivery of endoscopy training is required.